Evaluation of the surface thermal response of peripheral nerve blocks in dogs undergoing trauma or orthopedic surgery - Casas-Alvarado, Alejandro; Mota-Rojas, Daniel; Mora-Medina, Patricia; Martínez-Burnes, Julio; Hernández-Ávalos, Ismael; Zapata, Ana; Serra Aguado, C. Iván; Fernández-Parra, Rocío (Frontiers in Veterinary Science, 2025)
IntroductionLocoregional anesthesia using local anesthetics has been proposed as a highly selective method for perioperative acute pain management because it helps prevent the onset of noxious stimuli. However, a limitation of this technique is the possibility of nerve block failure. Infrared thermography (IRT) has been suggested as a non-invasive tool to assess the success of peripheral nerve blocks by detecting temperature changes related to vasodilation. This study aimed to evaluate the effect of peripheral nerve blocks on the superficial thermal response of limbs in dogs undergoing trauma or orthopedic surgery.MethodsA total of 26 dogs of various breeds, classified as ASA 1 or 2 and undergoing thoracic or pelvic limb, or abdominal surgery, were divided into two groups based on the analgesic technique used. In the experimental group [peripheral nerve block (PNB) n = 20], composed of animals undergoing trauma or orthopedic surgery, bupivacaine was infiltrated into the brachial plexus or the saphenous and sciatic nerves. The control group (n = 6) underwent general anesthesia and surgery, and they received conventional injectable analgesia. The variables assessed included maximum (Tmax), mean (Tmean), and minimum (Tmin.) temperatures of the axillary region, groin, and lateral femoral area, as well as rectal temperature (T°C). Measurements were taken at baseline (TBasal), and 5 (T5min.), 10 (T10min.), and 15 min (T15min.) after treatment.ResultsTmax, Tmean, and Tmin were significantly higher in the PNB group (by 2–3 °C) compared to the control group (p = 0.01). In the PNB group, superficial temperatures decreased by approximately 1 °C from baseline (p = 0.001), whereas the control group exhibited a greater decrease of approximately 3 °C at the same time points (p = 0.001). Rectal temperature was 2 °C higher in the PNB group compared to the control group (p = 0.01), although only the control group showed a progressive decrease over time (p = 0.05). No significant correlation was found between surface and rectal temperatures.DiscussionPeripheral nerve blocks with bupivacaine induced localized vasodilation, resulting in increased superficial heat radiation. This thermal response may serve as an indirect indicator complementary of nerve block effectiveness, supporting the use of IRT as a clinical tool to evaluate peripheral nerve block success in dogs. Further studies are recommended to confirm and validate its clinical application.